Cicatricial alopecia an approach to diagnosis and management - Price, Vera H.; Mirmirani, Paradi (Springer, 2011)
Written by leading world experts, Cicatricial Alopecia: An Approach to Diagnosis and Management is the first book on the diagnosis and treatment of primary cicatricial (scarring) alopecia. The book provides an in-depth discussion of the primary cicatricial alopecias. Initial chapters introduce the subject with detailed and systematic descriptions of clinical assessment of the patient, dermatopathology, medical management, and mechanisms and current research. The subsequent chapters follow a natural teaching format and begin with a clinical scenario of a patient and clues to the diagnosis, proceed to a general discussion that is extensively illustrated with clinical photographs, and end with practical take-away pearls and suggested readings for those who wish to pursue a topic in greater depth. A final chapter contains contributions by patients that highlight the frustration that many people with cicatricial alopecia experience in finding a physician who can accurately diagnose and treat their disorder. Dermatologists and dermatology residents and fellows, who are in search of a consummately practical and authoritative volume on the scarring alopecias, will find this book an indispensable addition to their clinical library.